Detection of aerolysin gene in Aeromonas hydrophila isolated from fish and pond water - Singh, Vijai (Springer-Verlag, 2009)
Aerolysin is a hemolytic toxin encoded by aerolysin gene (1482 bp) that plays a key role in the pathogenesis of Aeromonas hydrophila infection in fish. New speciesspecific primers were designed to amplify 326 bp conserved region of aerolysin gene for A. hydrophila. Twenty-five isolates of A. hydrophila recovered from fish and pond water were studied for detection of aerolysin gene. Aerolysin gene was detected in 85% of the isolates during the study. The designed primers were highly specific and showed no cross reactivity with Escherichia coli, Aeromonas veronii, Vibrio cholerae, Flavobacterium spp., Chyseobacterium spp. and Staphylococcus aureus. The sensitivity limit of primers for detection of aerolysin gene in the genomic DNA of A. hydrophila was 5 pg.